2018
DOI: 10.3847/1538-4357/aacbd7
|View full text |Cite
|
Sign up to set email alerts
|

Bridging Star-forming Galaxy and AGN Ultraviolet Luminosity Functions at z = 4 with the SHELA Wide-field Survey

Abstract: We present a joint analysis of the rest-frame ultraviolet (UV) luminosity functions of continuumselected star-forming galaxies and galaxies dominated by active galactic nuclei (AGNs) at z ∼ 4. These 3,740 z ∼ 4 galaxies are selected from broad-band imaging in nine photometric bands over 18 deg 2 in the Spitzer/HETDEX Exploratory Large Area Survey (SHELA) field. The large area and moderate depth of our survey provide a unique view of the intersection between the bright end of the galaxy UV luminosity function (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
72
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 39 publications
(91 citation statements)
references
References 75 publications
18
72
1
Order By: Relevance
“…The number density of faint AGN is close to that of the brightest Lyman-break galaxies (LBGs) observed, with the faint end of the AGN LF overlapping with the bright end of the galaxy LF as found by the SHELLQs (e.g. Matsuoka et al 2018), GOLDRUSH or SHELA survey (Stevans et al 2018). This overlap happens just around the luminosity regime probed by the objects investigated by Giallongo et al (2015) at z ∼ 4, who found in the COSMOS field a larger than expected number of AGN candidates of this magnitude or fainter.…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…The number density of faint AGN is close to that of the brightest Lyman-break galaxies (LBGs) observed, with the faint end of the AGN LF overlapping with the bright end of the galaxy LF as found by the SHELLQs (e.g. Matsuoka et al 2018), GOLDRUSH or SHELA survey (Stevans et al 2018). This overlap happens just around the luminosity regime probed by the objects investigated by Giallongo et al (2015) at z ∼ 4, who found in the COSMOS field a larger than expected number of AGN candidates of this magnitude or fainter.…”
Section: Introductionmentioning
confidence: 56%
“…Bouwens et al 2017;Livermore et al 2017;Ishigaki et al 2018, but see also Atek et al 2018 for a detailed analysis of the model uncertainties), and therefore that the number of faint galaxies able to produce ionizing radiation is large In the recent years, a lot of work has been dedicated to identify faint active galactic nuclei (AGN) in the highredshift Universe and determine their contribution to the reionization of the Universe (e.g. Giallongo et al 2015;Ricci et al 2017;Boutsia et al 2018;Parsa et al 2018;Matsuoka et al 2018;Stevans et al 2018). These AGN, while less luminous than bright quasars, could in principle be far more numerous.…”
Section: Introductionmentioning
confidence: 99%
“…Bouwens et al 2015;Finkelstein et al 2015), whereas other studies have suggested a rapid change in this parameter at z > 5 (e.g. McLure et al 2009McLure et al , 2013Bunker et al 2010;Wilkins et al 2011;Oesch et al 2012;Schenker et al 2013;Schmidt et al 2014;Bowler et al 2015;Stevans et al 2018;Viironen et al 2018).…”
Section: Introductionmentioning
confidence: 83%
“…To compensate we elect to use the data points from Bouwens et al (2015) for M UV ≥ −20 to allow for stronger constraints on the LBG faint-end slope. Furthermore, although our sample contains objects as bright as M UV ∼ −26, we do not have sufficient survey volume at this redshift to determine the position of the knee of the AGN LF at M UV −26.5 (Akiyama et al 2018;Stevans et al 2018). We therefore fit the AGN component of the LF with a single power law with the normalisation calculated at M UV = −25.7.…”
Section: Functional Forms Of the Fitsmentioning
confidence: 99%
See 1 more Smart Citation